desain, Sejarah, Budaya : Sebuah pengantar komprehensif / John A.Walker ; penerjemah, Laily Rahmawati ; editor, Maryam Bagus - WALKER, John A; laily Rahmawati; Maryam Bagus (Jalsutra, 2010)
xxxv, 268 hlm.: ilus.; 21 cm ( 3 eks)